Tertiary lymphoid structures in pancreatic cancer: a new target for immunotherapy - Zou, Xinlei; Guan, Canghai; Gao, Jianjun; Shi, Wujiang; Cui, Yunfu; Zhong, Xiangyu (Frontiers in Immunology, 2023)
Pancreatic cancer (PC) is extremely malignant and shows limited response to available immunotherapies due to the hypoxic and immunosuppressive nature of its tumor microenvironment (TME). Aggregation of immune cells (B cells, T cells, dendritic cells, etc.), which is induced in various chronic inflammatory settings such as infection, inflammation, and tumors, is known as the tertiary lymphoid structure (TLS). Several studies have shown that TLSs can be found in both intraand peritumor tissues of PC. The role of TLSs in peritumor tissues in tumors remains unclear, though intratumoral TLSs are known to play an active role in a variety of tumors, including PC. The formation of intratumoral TLSs in PC is associated with good prognosis. In addition, TLSs can be used as an indicator to assess the effectiveness of treatment. Targeted induction of TLS formation may become a new avenue of immunotherapy for PC. This review summarizes the formation, characteristics, relevant clinical outcomes and clinical applications of TLSs in the pancreatic TME. We aim to provide new ideas for future immunotherapy of PC.